The biology of the Cape Weaver Ploceus Capensis with special reference to its polygnous mating system - Elliott, Clive Christopher Hugh (Department of Biological Sciences, 2015)
The study of the biology of the Cape Weaver Ploceus capensis was carried out mostly in the winter rainfall area of the S. W. Cape in South Africa. This report shows that the species has conspicuous plumage dimorphism and some physical dimorphism in the sexes, and that the male only achieves full plumage at about 22 months old. The female reproduces at one year of age. Possible reasons for this deferred maturity in the male are discussed. It is concluded that the high competition for mates and the advantage to the young male in nest-building and territorial activities on the periphery of the colony are the main pressures for deferred maturity. A detailed investigation of breeding seasons in the species is reported and it is shown how aspects of the clutch-size and incubation strategy are apparent adaptations to polygyny and its concomitant fluctuating food source. The ultimate and proximate factors influencing the breeding season are also discussed. This study presents the first comprehensive study of moult in passerines in southern Africa. The more important findings are that moult is slower than in the northern hemisphere and that there are differences in the start of moult in different age/ sex classes. The food situation in the Cape Weaver is reported and it is shown how the species is adapted to a wide variety of insect and vegetable foods. The chicks are fed almost entirely on insect food except towards the end of the season. Weight fluctuations throughout the year are small and it is suggested that this shows that food fluctuations are smaller and present a much less difficult situation for the passerine in South Africa than in the northern hemisphere. Evidence is presented which shows a sex ratio of 1 : 1 in nestlings though there are some interesting tendencies revealed in the data. In full-grown birds, there is a slight excess of males probably throughout the year. It is pointed out that this is the opposite to what would be "required" by a polygynous mating system. Contrary to general theories, it is proposed that males do not suffer higher mortality than females during the breeding season. In fact it is suggested that females suffer higher mortality both in and out of the breeding season, partly as a result of their subordinate social position in all circumstances except at the nest. The territorial and courtship behaviour of the Cape Weaver are described and it is shown how aspects of the behaviours vary according to the time in the season and the pair-bond circumstances. A social hierarchy study on the species is discussed. Finally, the special aspect of the study, the unusual polygynous mating system is investigated in detail. A possible evolutionary sequence for the development of polygyny in passerines is proposed. This stresses the importance of the type of food source and the development of coloniality or gregariousness as the primary prerequisite. A feature of the thesis is the attempt to keep the theme of the adaptations to polygyny in mind through all the studies of the other parts of the Cape Weaver's biology.